Thermal Behaviour and Antimicrobial Activity of Novel Series of Benzoylthiourea Derivatives - Arslan, Hakan; Duran, Nizam; Ozlen Sahin, Nefise; Kulcu, Nevzat (Asian Journal of Chemistry, 2010)
Thermal behaviour and antimicrobial activity was investigated for a series of thiourea derivatives. The thermal behaviour of the compounds on heating up to 1000 K in nitrogen atmosphere was examined by thermogravimetry and differential thermal analysis. The compounds decompose in one or two stages. GC-MS combined system was used to identify the products during pyrolytic decompositions. The kinetic analysis of the thermogravimetric data was performed using the Coats-Redfern and Horowitz-Metzger methods. The antibacterial activities of these thiourea derivatives were investigated for three Gram positive (Enterococcus faecalis. Staphylocccus aureus and Staphylocccus epidermidis) and two Gram negative (Escherichia coli and Pseudomonas aeruginosa) bacteria by employing broth microdilution method and subsequently, inhibitory activity against yeast-like fungi (Candida albicans, Candida krusei, Candida glabrata and Candida parapsilosis) was also determined. Only three of the compounds showed antimicrobial activity and that were at a moderate level. None of them exhibited sufficient antifungal activity to become a drug candidate.